A hydro-mechanical coupled analysis of rainfall induced landslide using a hypoplastic constitutive model. (August 2019) - Tang, Yang; Wu, Wei; Yin, Kunlong; Wang, Shun; Lei, Guoping
Abstract: We present a hydro-mechanical coupled analysis for the long-term behavior of rainfall induced landslide. A simple hypoplastic model is used to describe the strain softening behavior of soil. The model requires only few parameters, which is advantageous when scarce data are available. The constitutive model is implemented in a finite element code. The numerical model is used to simulate a well-documented landslide, the Baishuihe landslide in South China. Some emphasis is given to the step-like deformation behavior, which is dictated by the rainfall characteristics and the strain softening behavior of soil. Two rainfall types with different intensity and duration are considered.